Sergiy Semenovych Strafun - of Orthopedic Traumatologists, Ukrainian Association (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2020)
The article is dedicated to the 60th anniversary of the honored worker of science and technology of Ukraine, laureate of the State Prize of Ukraine in the field of science and technology, deputy director for research at the Institute of Traumatology and Orthopedics of the National Academy of Medical Sciences of Ukraine, head of the department of microsurgery and reconstructive surgery of the upper limb, doctor of medical sciences of professor corresponding member of NAMS of Ukraine Strafun S. S.